Bunker procurement strategies of liner companies part II financial strategies to tackle volatile bunkers - Goh, Weihan. (2011)
Bunkers are predominantly one of the main drivers of the shipping industry. Without them, vessels would be unable to carry out daily operations and the maritime industry would come to a grinding halt. However, as much as businesses are dependent on bunkers, this dependence poses a major problem to them, especially those in the operation of liners. Bunkers are distillates of crude oil, thus sharing a direct relation to the crude’s volatility, which hit highs following the 2008 and 2009 recession and more recently in April 2011. Furthermore, an increased focus on carbon footprint reduction in the maritime industry has led to the need in burning low sulphur but higher costing bunkers in certain areas. In view of the situation, liner businesses are facing the mounting pressure to identify ways to lower bunker procurement costs. Hence this dissertation will review and evaluate current measures in place with the aim to propose a holistic solution of through operational and risk management aspects.